Deep trade agreements and cross-border innovation collaboration: Evidence from ASEAN - Vorraakkatham, Phukkhaphob; Ariyasajjakorn, Danupon (Asian Journal of Economic Modelling, 2026)
This study investigates whether deeper regional trade agreements (RTAs) increase the likelihood of co-patenting activities between ASEAN nations and innovative partners, addressing a potential gap in the literature. Unlike prior studies, we construct indices capturing co-invention and co-application of patents based on the fractional patent counting approach. A gravity-like model of cross-country technological collaboration is developed, incorporating fixed effects to account for unobserved heterogeneities at the country-pair level and time-varying characteristics that may influence cross-border links. The baseline results suggest that, although the static positive effects of trade integration on joint innovation activities are not immediately evident, agreements with a broader scope tend to promote such activities, particularly in the case of co-invention of patents. Sensitivity analyses indicate that RTAs containing provisions related to innovation are more likely to foster intra-bloc collaboration among signatories. Additionally, dynamic analysis reveals anticipation and phasing-in effects of trade policy changes, as evidenced by estimates of leads and lags in trade agreement indices. Overall, the findings demonstrate that deep trade integration has both short-term and long-term positive effects on collaborative innovation activities.